Dichloridobis(2-chlorobenzyl)tin(IV) - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
Molecules of the title compound, [Sn(C(7)H(6)Cl)(2)Cl(2)], lie on a twofold rotation axis which passes through the Sn atom. The SnIV atom exists in a distorted tetrahedral geometry. Adjacent molecules are linked by weak Sn...Cl contacts [3.703 (1) A], forming a linear chain motif extending along the b axis.